Background review for the '2020 European guideline for the diagnosis and treatment of gonorrhoea in adults'. (February 2021) - Unemo, M; Ross, JDC; Serwin, AB; Gomberg, M; Cusini, M; Jensen, JS
Gonorrhoea is a major public health concern globally. Increasing incidence and sporadic ceftriaxone-resistant cases, including treatment failures, are growing concerns. The 2020 European gonorrhoea guideline provides up-to-date evidence-based guidance regarding the diagnosis and treatment of gonorrhoea. The updates and recommendations emphasize significantly increasing gonorrhoea incidence; broad indications for increased testing with validated and quality-assured nucleic acid amplification tests (NAATs) and culture; dual antimicrobial therapy including high-dose ceftriaxone and azithromycin (ceftriaxone 1 g plus azithromycin 2 g) OR ceftriaxone 1 g monotherapy (ONLY in well-controlled settings, see guideline for details) for uncomplicated gonorrhoea when the antimicrobial susceptibility is unknown; recommendation of test of cure (TOC) in all gonorrhoea cases to ensure eradication of infection and identify resistance; and enhanced surveillance of treatment failures when recommended treatment regimens have been used. Improvements in access to appropriate testing, test performance, diagnostics, antimicrobial susceptibility surveillance and treatment, and follow-up of gonorrhoea patients are essential in controlling gonorrhoea and to mitigate the emergence and/or spread of ceftriaxone resistance and multidrug-resistant and extensively drug-resistant gonorrhoea. This review provides the detailed background, evidence base and discussions, for the 2020 European guideline for the diagnosis and treatment of gonorrhoea in adults (Unemo M, et al. Int J STD AIDS. 2020).